The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1978
DOI: 10.21273/hortsci.13.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mechanized System for Production, Harvesting and Handling of Strawberries1

Abstract: A completely mechanized system for production, harvesting and handling strawberries (Fragaria × anassa Duch.) for processing is described. Pre-harvest cultural factors, including bed preparation, plant population, harvest date and clonal evaluation and adaptability to mechanical harvesting, were studied for 4 years. ‘Cardinal’, ‘Earlibelle’, and Arkansas breeding line A-5344 were well suited for once-over mechanical harvesting under Arkansas conditions considering yield, quality, and organoleptic evaluation. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Several harvesting principles were evaluated in the process of developing a mechanical harvester for strawberries at the University of Arkansas (43,63,74,75,76,77). One approach included cutting or clipping fruit from the plant, but a majority of the large fruit was not harvested since they were on the ground.…”
Section: Strawberriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Several harvesting principles were evaluated in the process of developing a mechanical harvester for strawberries at the University of Arkansas (43,63,74,75,76,77). One approach included cutting or clipping fruit from the plant, but a majority of the large fruit was not harvested since they were on the ground.…”
Section: Strawberriesmentioning
confidence: 99%
“…Work at the University of Arkansas has shown that certain straw berry clones (e.g., 'Cardinal' and A-5344) are more adapted to machine harvesting, cleaning, and sorting without loss of quality (63,64,66,68,76,77). These cultivars have concentrated ripening patterns and firm fruit.…”
Section: Strawberriesmentioning
confidence: 99%
See 3 more Smart Citations